Brivaracetam as adjunctive treatment for uncontrolled partial epilepsy in adults: A phase III randomized, double‐blind, placebo‐controlled trial. Issue 1 (8th November 2013) - Biton, Victor; Berkovic, Samuel F.; Abou‐Khalil, Bassel; Sperling, Michael R.; Johnson, Martin E.; Lu, Sarah
Summary Purpose Brivaracetam (BRV) is a novel high‐affinity synaptic vesicle protein 2A ligand currently being investigated for the treatment of epilepsy. The purpose of this phase III study was to evaluate the efficacy and safety/tolerability of adjunctive BRV in adults with uncontrolled partial‐onset (focal) seizures. Methods This was a prospective, multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group, fixed‐dose trial (N01253; NCT00464269). Adults aged 16–70 years with well‐characterized partial epilepsy not fully controlled despite treatment with one or two antiepileptic drugs (AEDs) were enrolled. Patients who experienced eight or more partial‐onset seizures, whether or not secondarily generalized, during the 8‐week prospective baseline period were randomized (1:1:1:1) to receive twice‐daily placebo (PBO) or BRV (5, 20, or 50 mg/day) without titration. The primary efficacy endpoint was percent reduction over PBO in baseline‐adjusted partial‐onset seizure frequency/week during the 12‐week treatment period. Comparison of BRV with PBO was sequential (50, 20 mg/day, then 5 mg/day). Secondary endpoints included ≥50% responder rate and median percent reduction from baseline in partial‐onset seizure frequency/week. Post hoc analyses included the primary efficacy endpoint evaluated over 28 days and exploratory subanalyses of efficacy by seizure subtype. Safety and tolerability assessments included treatment‐emergent adverse events (TEAEs), laboratory tests, electrocardiography, vital signs, and physical and neurologic examinations. Key Findings Of 400 patients randomized, 396 were included in the intent‐to‐treat (ITT) population (PBO n = 98, BRV 5 mg/day n = 97, BRV 20 mg/day n = 100, BRV 50 mg/day n = 101) and 392 comprised the modified ITT (mITT) population. A total of 361 (91.2%) of 396 patients completed the study. Most patients (78.3%) were receiving two concomitant AEDs. Percent reduction in partial‐onset seizure frequency/week over PBO was −0.9% (p = 0.885) for BRV 5 mg/day, 4.1% (p = 0.492) for BRV 20 mg/day, and 12.8% (p = 0.025) for BRV 50 mg/day (mITT population). Statistical significance was also achieved for the percent reduction over PBO in baseline‐adjusted partial‐onset seizure frequency/28 days for BRV 50 mg/day (22.0%; p = 0.004) but not for the other BRV dose groups. In the BRV 50 mg/day group, statistical significance was also seen for the ≥50% responder rate (BRV 32.7% vs. PBO 16.7%; p = 0.008) and median percent reduction from baseline in partial‐onset seizure frequency/week (BRV 30.5% vs. PBO 17.8%; p = 0.003). In the exploratory subanalysis by seizure subtype, median percent reduction from baseline in seizure frequency/week and ≥50% responder rate were numerically greater than PBO in the BRV 20 and 50 mg/day groups for simple partial, complex partial, and secondarily generalized seizures. BRV was generally well tolerated, with the majority of TEAEs being mild‐to‐moderate in intensity. Of the TEAEs reported by ≥5% patients, those with a frequency >3% higher than PBO for any dose of BRV compared with PBO were somnolence, dizziness, fatigue, influenza, insomnia, nasopharyngitis, vomiting, diarrhea, urinary tract infection, and nausea. Significance Adjunctive BRV at a daily dose of 50 mg was associated with statistically significant reductions in seizure frequency compared with PBO. All doses of BRV showed good tolerability throughout the study.